Contrast‐Enhanced Ultrasound (CEUS) as predictor for early retear and functional outcome after supraspinatus tendon repair - Kunz, Pierre; Mick, Paul; Schmidmaier, Gerhard; Zeifang, Felix; Fischer, Christian (Journal of orthopaedic research, 2020)
Supraspinatus (SSP) tendon tears represent a common indication for shoulder surgery. Yet, prediction of postoperative function and tendon retear remains challenging and primarily relies on morphologic magnetic resonance imaging (MRI)‐based parameters, supported by patients' demographic data like age, gender, and comorbidities.